2023
DOI: 10.1093/plphys/kiad250
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinium as a comparative system for understanding of complex flavonoid accumulation profiles and regulation in fruit

Abstract: The genus Vaccinium L. (Ericaceae) contains premium berryfruit crops including blueberry, cranberry, bilberry and lingonberry. Consumption of Vaccinium berries is strongly associated with various potential health and many of these benefits are attributed to the relatively high concentrations of flavonoids, including the anthocyanins that provide the attractive red and blue berry colours. Since these phytochemicals are increasingly appealing to consumers, they have become a crop breeding target. There has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 131 publications
0
7
0
Order By: Relevance
“…The biosynthesis of flavonoid has been well-documented from a molecular genetic perspective [28,29]. Chalcone isomerase (CHI) catalyzes the conversion of colorless chalcones to flavanone (naringenin).…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthesis of flavonoid has been well-documented from a molecular genetic perspective [28,29]. Chalcone isomerase (CHI) catalyzes the conversion of colorless chalcones to flavanone (naringenin).…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthesis of flavonoids has been well documented from a molecular genetic perspective [30,31]. Chalcone isomerase (CHI) catalyzes the conversion of colorless chalcones to flavanone (naringenin).…”
Section: Discussionmentioning
confidence: 99%
“…The comparative analysis showed that the flavonol content of cranberry fruit samples harvested from five oligotrophic habitats was higher than that of samples harvested from five eutrophic or mesotrophic wetland habitats [15]. Albert et al suggested that flavonol biosynthesis is influenced by light in plants, vegetative organs, developing flowers and fruits, and covering tissues (including UVA and UVB) [31]. In oligotrophic wetland habitats, cranberry groves are located in more open areas.…”
Section: Analysis Of the Qualitative And Quantitative Composition Of ...mentioning
confidence: 99%